Recruitment of Beneficial M2 Macrophages to Injured Spinal Cord Is Orchestrated by Remote Brain Choroid Plexus - Shechter, Ravid; Miller, Omer; Yovel, Gili; Rosenzweig, Neta; London, Anat; Ruckh, Julia; Kim, Ki-Wook; Klein, Eugenia; Kalchenko, Vyacheslav; Bendel, Peter; Lira, Sergio A.; Jung, Steffen; et al. (Immunity (Cambridge, Mass.), 2013)
Monocyte-derived macrophages are essential for recovery after spinal cord injury, but their homing mechanism is poorly understood. Here, we show that although of common origin, the homing of proinflammatory (M1) and the “alternatively activated” anti-inflammatory (M2) macrophages to traumatized spinal cord (SC) was distinctly regulated, neither being through breached blood-brain barrier. The M1 macrophages (Ly6chiCX3CR1lo) derived from monocytes homed in a CCL2 chemokine-dependent manner through the adjacent SC leptomeninges. The resolving M2 macrophages (Ly6cloCX3CR1hi) derived from monocytes trafficked through a remote blood-cerebrospinal-fluid (CSF) barrier, the brain-ventricular choroid plexus (CP), via VCAM-1-VLA-4 adhesion molecules and epithelial CD73 enzyme for extravasation and epithelial transmigration. Blockage of these determinants, or mechanical CSF flow obstruction, inhibited M2 macrophage recruitment and impaired motor-function recovery. The CP, along with the CSF and the central canal, provided an anti-inflammatory supporting milieu, potentially priming the trafficking monocytes. Overall, our finding demonstrates that the route of monocyte entry to central nervous system provides an instructional environment to shape their function. [Display omitted] ► Breached BBB is not a preferred entry route for monocytes infiltrating injured SC ► M2 macrophage homing to injured SC is orchestrated by the brain choroid plexus ► The choroid plexus and CSF provide trafficking monocytes with an M2-biased milieu ► M1 macrophages home to injured SC via leptomeninges, in a CCL2-dependent manner